Morphometric analysis revealed two different Mediterranean horse mackerel (Trachurus mediterraneus) stocks in the Adriatic Sea - Claudio Vasapollo (PeerJ)
Phenotypical differentiation among individuals of Mediterranean horse mackerel Trachurus mediterraneus in the Adriatic Sea was investigated through the analysis of several morphometric characters. Overall, 426 individuals of Mediterranean horse mackerels were sampled from the northern, central and southern Adriatic Sea during the summers of 2012 and 2013. Forty-six morphometric characters were measured for each individual and then compared using multivariate techniques (linear discriminant analysis). Based on the morphometric characteristics, at least two different Mediterranean horse mackerel were identified: one comprising the northern and central Adriatic, and the other formed by individuals from the southern Adriatic basin. The northern and central areas showed stable populations, overlapping both in space and time. The southern area seemed to be more variable over the years, with a low degree of overlapping both in space and time. A possible hypothesis for this, to be further investigated, could be the flow of individuals from the Ionian and Aegean Seas populations through the Otranto Channel. The main differences between the two stocks were associated with the head characters of the fish. In particular, the northern and central Adriatic Sea individuals had shorter and thicker heads than the southern ones. This could be due to different feeding habits: the former mainly feed on small fishes, the latter mainly on euphausiids. A short mouth could reduce the power of suction of bigger preys, while a long mouth could increase the volume of water to be filtered to feed on small planktonic crustaceans. From this study, it becomes clear that the Mediterranean horse mackerel should not be managed as a single stock in the Adriatic Sea as it was evident that at least two morphologically different stocks are present in the basin.